PENGARUH KUALITAS INFORMASI AKUNTANSI MANAJEMEN DALAM PENGAMBILAN KEPUTUSANTERHADAP KINERJA KEUANGANRUMAH SAKIT - Sri Astuti Musaid (JURNAL MANEKSI, 2016)
This study aims to analyzing the quality of management accounting information in deciding on financialperformance in public hospital in Ambon and Maluku Tengah. The date collection used survey by deliveringquestionnaires. From 44 samples of the respondents that had been delivered to the leaders, vice director, head ofeach division in hospitals (RSUD Dr. Haulussy Ambon, RSUD Tulehu and RSUD Masohi) 42 was used toanalyze the date. The analysis method regration. The result of the study shows that the quality of the accountingmanager information and the decision making has positive and significant correlation. It is also an apparent thatthe financial performance was influenced by the quality of accounting manager. However, the manager qualityhas no influence over the decision making whereas the quality of information accounting manager has positiveinfluence towards the financial performance.